Short and medium term approaches and measures to solving Africa's debt problem - Ahmed, A.; Ahmed, Abdulkadir (Lagos: Central bank of Nigeria (CBN), 1988)
This is an address made by the Governor of the Central Bank Abdulkadir Ahmed at the Financial TImes Conference on "the challenge to recovery and growth, finding solutions to Africa's external debt, in London, April 18-19, 1988.
lje 14/3/19
Arch
Keywords: Government Dept; External Debt; Africa